CODESRIA Bulletin Online, No. 1, February 2025 - Why France Can’t Be Nigeria’s Strategic Partner - Bangura, Yusuf (CODESRIA Bulletin, 2025)
I’ve seen and listened to many responses – some direct, others indirect – to my article1 on the problems of Nigeria’s foreign policy, which looked at Nigeria’s assigned role in BRICS as a ‘partner member’ and its new-found love of France. That article has been widely circulated on Facebook and WhatsApp as well as in a number of online Nigerian newspapers, including Premium Times, Daily Trust and Intervention. It portrays Nigeria’s decision to join BRICS as a partner member as an indication of its declining role in world affairs and its pursuit of a transactional approach in the conduct of its foreign policy. It also questions Nigeria’s full embrace of France (a historical rival) as a regional partner at a time when hatred for French neocolonial policies in Francophone Africa is at an all-time high. Two articles, one by Muhammad Al-Ghazali (in Daily Trust)2 and another by Toba Alabi (in Future World),3 a professor of political science and defence studies at the Nigerian Defence Academy, fully supported my arguments'. Bolaji Akinyemi, the doyen of Nigerian foreign policy, also questioned Nigeria’s partner member status in BRICS in an interview he gave on Channels TV on Trump’s inaugural lecture.4 However, Mukhtar Imam,5 a professor of international relations and diplomacy at Al- Muhibbah Open University in Abuja, disagreed with me. He raised several points, many of them muddled and superficial or not thought through. The crucial point I take from his intervention is that, in a rapidly changing world, Nigeria should weigh its options carefully before fully committing itself to global power blocs. And, given Nigeria’s weak economy, a pragmatic approach that would enable the country to attract trade and investments would be most appropriate for Nigeria’s foreign policy. Nigeria’s foreign minister, Yusuf Tuggar – though not directly responding to my article – has also emphasised Nigeria’s overlapping interests and need for pragmatism in pursuing the country’s economic and strategic interests, in his article on Premium Times6 and in an interview he gave to Bloomberg at Davos in January 2025. He referenced Africa as the centrepiece of Nigeria’s foreign policy and affirmed that Nigeria’s size gave it the added responsibility to be the regional power or hegemon in West Africa. In the Davos interview, Tuggar also questioned the media’s critical responses to Nigeria’s partner member status in BRICS. He affirmed, in his article and the interview, that the foreign policy doctrine of Bola Ahmed Tinubu, or Nigeria, is ‘strategic autonomy’, which, he proffered, abhors the presence of foreign military forces in West Africa. This doctrine seems to convey a shift towards a transactional approach to foreign policy, in the sense of giving Nigeria the freedom to transact deals with countries around the world. He did not, however, define what exactly ‘strategic autonomy’ means. Autonomy from what or from whom? What Nigeria does in practice may provide clues. In 2023, just after taking office, Tuggar announced a 4D foreign policy doctrine (democracy, development demography and diaspora), which he christened the ‘4D Tinubu Doctrine’ on foreign policy. This doctrine has generated wide-ranging critical reviews by foreign policy experts and pundits, many pointing out its lack of clarity on how the four Ds will impact Nigeria’s conduct of foreign policy. The four Ds do look more like topics than a doctrine. How, for instance, can Nigeria defend or support democracy in its foreign policy when it suffers from a huge democracy deficit at home? Its party system is broken, or antidemocratic; it cannot consistently organise credible, free and fair elections; and citizens are arrested and detained for libel for criticising well- connected and influential people. Indeed, Nigeria scores poorly or below average in most global indexes that track democracy and governance. Femi Mimiko, a professor of political science at the Obafemi Awolowo University, notes that the 4Ds are ‘rather too fluid in conception, too broad in scope, and too woolly in objective’.7 Regardless, the idea of pragmatism, or working with all major powers and blocs in a transactional way, seems to define Tuggar’s and Tinubu’s approach to foreign policy. I’ve watched a few interviews on Nigerian television in which the issue of pragmatism has been raised to justify the partner member role granted to Nigeria in BRICS and deepening relations with France. In this article, I want to demonstrate why France cannot be a strategic partner for Nigeria and the dangers of pursuing a transactional foreign policy that is devoid of a strategic anchor. I will first show why pragmatism is a meaningless concept in the study of international politics, then provide, in two sections, a historical overview of Nigeria’s foreign policy and France’s Africa policy. Subsequent sections explain why Nigeria’s relations with France are bound to be conflictual and discuss Nigeria’s dysfunctional and transactional domestic politics and the dangers of transactionalism in the conduct of foreign policy. All states are pragmatic in foreign policy Pragmatism doesn’t really tell us what a state’s foreign or strategic policy is because all states are pragmatic. The first thing one learns in the study of global politics or strategic studies is that ideology, which is the opposite of pragmatism, plays little or no role in the foreign-policy calculations of states. The world system is largely anarchical. In other words, it has no central government, even though it has created a global institution, the UN, which tries to play that role, and there are norms, treaties and laws that seek to regulate the behaviour of states in the international system. The values or ideologies that inform domestic state practices may be useless in an environment where states are trying to survive and defend or advance their interests globally. States may profess or uphold certain values, norms or ideologies, but these are rarely the prism through which they interpret, or behave, in the world, especially if they are seen as an obstacle to the realisation of their core objectives. Look at the examples of the US and the Soviet Union, arch rivals with diametrically opposed values, systems of government and ideologies. During the Cold War, both countries worked with and supported regimes that did not share their ideological beliefs in their struggle for dominance in the world. At the end of the Cold War, the US and its Western allies projected an ideology of liberal internationalism (the spread of democracy, human rights and markets on a world scale), when the US became dominant in what came to be called a unipolar world. It did this because it had no credible opposition and could do as it pleased in the world. That period of hegemony has now ended. However, copious studies show that even in the heydays of that policy, the West’s support for global democracy was selective. And in the current period, the West cannot uphold even the central feature of its ideology on markets and capitalism – the free global movement of goods and capital – as the US slams tariffs on China’s, Mexico’s and Canada’s exports and imposes restrictions on the sale of advanced semiconductor chips to China. The strategic policy that informs the protectionist behaviour towards China is containment – to prevent China from dominating the world. This is unvarnished great power politics, not ideological rivalry. The same can be said for the Soviet Union and China, with their ideologically driven communist systems of government. Regarding the Soviet Union, apart from its expansionist activities in Eastern Europe, when it played an active role in building communism in those countries, Soviet foreign policy in the wider world was not revolutionary. Indeed, even Soviet expansionism in Eastern Europe could be seen as a strategic move to provide a buffer between itself and the more powerful western European and US alliance, NATO, which was steadfast in trying to contain or destroy its communist system. The Soviets were interested in defending the communism they had built in their own country by cultivating friends overseas, irrespective of their ideological inclinations. Their foreign policy was pragmatic within the context of protecting Soviet communism and challenging Western global hegemony. There were no Soviet revolutionaries or ideologues running around the world spreading socialism or communism. The Soviets supported left-leaning states that were opposed to Western hegemony as well as conservative or neutral states that were open to doing business with them. Soviet embassies were not filled with revolutionaries but had spies, just as the US and other major powers did, who helped to provide intelligence and enhance the power of the Soviet Union globally. Let me give two examples that I witnessed when I taught in Nigeria in the 1980s. Under the leadership of Bolaji Akinyemi, the Nigerian Institute of International Affairs (NIIA) held a roundtable discussion on Soviet–Nigeria relations and Akinyemi invited me to prepare a lead paper on the Soviet Union’s economic relations with Africa. I gave it my all. I thought I was fair to the Soviet economic system and its trade relations, even though I raised some critical issues. However, the Soviet representatives at the meeting were unhappy with the paper. During the evening cocktail before the roundtable, two members of the Soviet embassy pulled me aside and took me to the back of the room. They strongly protested about what I had written, asked me what I wanted, and told me to withdraw the paper. I responded that what they demanded wouldn’t be done and that if they had any issues with the paper, they should raise them at the roundtable. The following day, my paper was the first to be tabled for discussion. The Soviet ambassador and a large contingent of Soviet officials were in the meeting. I recall that my presentation was methodical and forceful because I had prepared well after my encounter with the Soviet officials the previous evening. When the chair asked for comments, the Soviet ambassador remarked only that the paper was full of factual errors but could not highlight any, and asked the NIIA to schedule another roundtable to which he would invite scholars from the Soviet Union to challenge what I had written. I was left with the impression that the Soviet embassy had spies masquerading as policy professionals. My next encounter with Soviet officials in Nigeria was during the Marx and Africa conference at the Ahmadu Bello University in 1983. I was a member of the steering committee. On the eve of the conference, we were approached by two officials from the Soviet embassy in Lagos, who asked us to give them the list of participants for the conference. We politely told them that it was not our policy to provide lists of participants to individuals who were not members of our group. We thought we would see them at the conference the following day, but they left the campus after we rejected their request. They were not interested in the ideas that were going to be discussed at the conference. They wanted only the list of participants for their political work. What all this suggests is that, by necessity, all states behave pragmatically in the world system in their struggle to survive or be influential and powerful. Big states, or those with great power ambitions, seek hegemony in their own regions and try to prevent other powerful states with great power ambitions from becoming hegemonic at the global level. Small states with no great power ambitions tread cautiously by not offending the great powers or seek protection from one of the great powers by becoming vassal states. Power and interests – not pragmatism, which every state practises – are a powerful prism through which to understand the foreign and strategic policies of states. John Measheimer, the leading realist scholar in international relations, describes in The Tragedy of Great Power Politics8 how before the US became a superpower it first became a regional power or hegemon in the Western hemisphere. It did this by expelling all European imperial powers (British, Spanish, Portuguese, French and Dutch) and imposing the Monroe Doctrine on them – signalling clearly that the Western hemisphere was the US’s backyard or sphere of influence and it would go to war to defend it. This was why John Kennedy used the strategic policy of madness (what Thomas Schelling9 called ‘the rational use of irrationality’) to eject the Soviet Union’s nuclear missiles from Cuba in 1962, threatening to uproot them even if his actions led to a nuclear war with the Soviet Union in which both states would perish. The key point in all of this, as Measheimer points out, is that big powers always try to protect their immediate region by becoming the regional hegemon. Nigeria’s foreign and strategic policy By virtue of the size of its population and economy, vis-à-vis other African countries, Nigeria has historically seen itself as the Giant of Africa. It has, over many decades, developed strategies and policies that seek to enhance its ambition to become a regional power and an important state in the world system. However, the crafting of Nigeria’s strategic policy of greatness lagged its actual practice of projecting regional power status. The oil boom of the early 1970s ignited confidence among policymakers that Nigeria was destined for greatness. There was a range of big and well-funded policy initiatives on, among other projects, industrialisation, economic indigenisation, large-scale agricultural development and promotion of national unity schemes, such as the National Youth Service Corps. It is not surprising that Phillip Asiodu, one of the Super Permanent Secretaries at the time, described the raft of big policy initiatives that Nigeria embarked upon in the 1970s as ‘The Nigerian Revolution’.10 The oil boom was a shot in the arm for Nigerian leaders to forcefully project an Africa- centred policy, starting with Murtala Mohammed when he seized power in 1975 from Yakubu Gowon and decided to strongly support the liberation movements in southern Africa. Mohammed openly denounced US president Gerald Ford’s policies on Angola, resisted his pressures, and unequivocally threw Nigeria’s support behind the People’s Movement for the Liberation of Angola (MPLA), which was waging an armed struggle against Portuguese colonialism. Nigeria was even made a frontline state in the fight against apartheid and Portuguese colonial rule in Angola and Mozambique, despite being thousands of kilometres away. In 1976, during the regime of Olusegun Obasanjo, Murtala Mohammed’s successor, Nigeria established a Southern Africa Relief Fund, which attracted donations not only from the government but also from citizens. It has been reported that Nigerian civil servants contributed 2 per cent of their salaries to that fund.11 Nigeria also issued more than 300 passports to black South Africans to enable them to travel abroad. Nomfundo Ngwenya, writing on the online platform of the South African Institute of International Affairs (SAIIA) in 2010, reported that Nigeria had spent an estimated USD 61 billion in supporting the frontline states by the end of apartheid in 1994.12 It should be noted that anti-imperialist and anti-apartheid sentiments were strong in Nigeria even during the leadership of Abubakar Tafawa Balewa (1960–1966), who was generally regarded as conservative. His decision to sign the infamous Anglo-Nigerian Defence Agreement in 1960, just after independence, generated strong popular protests that led to its abrogation in 1962.13 However, Balewa adopted an uncompromising position on the question of apartheid and African liberation. The Sharpeville Massacre of sixty-nine black people in South Africa, in the same year that Nigeria gained independence, may have radicalised him on the issue of apartheid. Balewa lobbied for South Africa’s expulsion from the Commonwealth and provided annual financial assistance of USD 5 million to the African National Congress (ANC) and the Pan-Africanist Congress (PAC).14 Prior to the Mohammed and Obasanjo regimes’ pro-active Africa-wide initiatives, Yakubu Gowon had taken the crucial step of pushing for the creation of the Economic Community of West African States (ECOWAS) in 1975 through his able minister of economic development and post-war reconstruction, Adebayo Adedeji, whom Francophone West African policymakers referred to as ‘le Père de la CEDEAO’ (the Father of ECOWAS).15 The ECOWAS project was launched to support Nigeria’s industrialisation, advance its influence in West Africa and wean the Francophone African states from France, which had supported the breakup of Nigeria during the civil war of the 1960s. Gowon was smart in choosing a Francophone African leader, Gnassingbé Eyadema of Togo, as a partner in launching the project. Even though Nigeria accounts for half of the population of West Africa (English- speaking West Africa accounts for about 60 per cent) and more than 60 per cent of its GDP (before the devaluation of the naira in 2023–2024), nine of the sixteen states in West Africa are Francophone. The Francophone states also account for about 90 per cent of the region’s land mass. It was important, therefore, that Nigeria worked with a Francophone country to advance its regional integration project. By the end of the 1970s, the broad outline of Nigeria’s foreign and strategic policy had clearly emerged in the practical field of interstate relations. The logic of that activist foreign policy was primarily that Nigeria must project its power in its immediate environment or become the regional hegemon in West Africa, while acting as the voice of Africa within Africa and the world at large. It was Ibrahim Gambari,16 the foreign minister of the regime of Muhammadu Buhari between 1984 and 1985, who translated this evolving practice into a theoretical or strategic scheme by situating Nigeria’s foreign policy within a framework of what he called ‘three concentric circles’. The first circle was the homeland, or Nigeria; the second was West Africa; and the third was wider Africa. Prior to his job as foreign minister, Gambari had played a lead role in establishing an international studies programme at the Ahmadu Bello University, which made the study of French or Arabic compulsory for students who enrolled in the programme. Study tours to Francophone countries, such as Togo, were organised to get students to understand the Francophone West African world. I joined that programme in its first year in 1980, the year that I was recruited into the university and oversaw the courses dealing with international political economy. When Bolaji Akinyemi17 took over the reins of the ministry of foreign affairs during the early years of Ibrahim Babangida’s regime (1985–1987), the understanding of Nigeria’s foreign policy in terms of the three concentric circles was well established. Akinyemi tried to project Nigeria’s power a step further. Trained as a realist at the Fletcher School of Law and Diplomacy and at the University of Oxford, he had a vision of Nigeria as a great power and seemed determined to push it. As director general of the NIIA, during the radicalisation of Nigeria’s foreign policy under Murtala Mohammed, he organised a major conference of Nigerian scholars in 1976 to discuss Nigeria’s place in the world. Confident that Nigeria was already a regional West African power and a force to be reckoned with in Africa, when Akinyemi became foreign minister in 1985 he sought to project Nigeria’s power further by advocating a ‘concert of global medium powers’, which included countries as diverse as Algeria, Argentina, Austria, Brazil, Egypt, India, Indonesia, Malaysia, Mexico, Senegal, Sweden, Switzerland, Venezuela, Yugoslavia and Zimbabwe. This resulted in The Lagos Forum in 1987, a conference of medium powers drawn from across four major regions of the world. During Akinyemi’s tenure, he also launched the Nigerian Technical Aid Corps to provide African, Caribbean and Pacific countries with technical support in various fields, including education, medicine, engineering, agriculture, technology, law, architecture and artisanship. Nigeria’s Africa-centred activist foreign policy earned it a de facto permanent seat on the African Union’s Peace and Security Council, which was established in 2004. With Egypt, it is the only African country that has been elected five times as a non-permanent member on the UN Security Council. Nigeria’s projection of big-power status, or regional hegemony, came to a head in the 1990s, during the regime of Ibrahim Babangida when, through an ECOWAS military force (which become known as ECOMOG), he sent Nigerian troops to Liberia to pacify the warring factions in that country’s civil war.18 ECOMOG’s operations were expanded in Liberia and extended to Sierra Leone during the brutal dictatorship of Sani Abacha to prevent those countries from sliding into protracted anarchy. Those interventions were a burden on the Nigerian treasury but they underscored Nigeria’s big-power status in the region and provided the internationally despised Abacha regime with a bargaining chip in dealing with the West and its criticism of his regime. They also set the stage for a radical transformation of ECOWAS, from an organisation that was concerned only with economic integration into one that also prioritises regional peace and security. The outcomes of most of these initiatives were far less impressive than expected. I raise them to demonstrate the vision that earlier thinkers and actors in the foreign policy field had for Nigeria’s significance in Africa and the world and for the need to act strategically when conducting foreign policy. There is a fairly broad consensus among observers of Nigeria’s foreign policy that over the past fifteen or so years Nigeria has lost its mojo in African and wider world politics.19 This has been traced to its economic difficulties, long-running multiple insecurities, troubled or dysfunctional domestic politics, widespread mistrust of the federal state, and election of leaders with limited interest in, or knowledge about, foreign policy. A state of inertia or lack of strategic direction has set in as the country grapples with its internal problems. France’s Africa policy Much has been written on France’s Africa policy, which, especially in recent times, focuses on the neocolonial relations it established with its ex-colonies in the domains of economy, defence, bureaucracy and culture. France’s economic relations with its ex-colonies are governed by a monetary regime that initially tied the currencies of those countries (the CFA francs issued by the West and Central Francophone African central banks)20 to the French franc and subsequently to the euro. The Franco-African monetary regime also required the banks of the two currency blocs to deposit their reserves in the French treasury, and for a very long time a French government representative sat on the boards of those banks.21 These arrangements allowed France to maintain a firm grip on the economies of the Francophone African countries and dominate their external trade and investment relations. France also controlled their defence policies by establishing military bases in key countries, such as Côte d’Ivoire, Senegal, Niger, Mali, Burkina Faso, Chad, Gabon and Djibouti. In addition, many French citizens work in those countries’ bureaucracies and France extensively lobbies for their elites to secure important positions in international organisations. The term Françafrique has been used to describe this neocolonial relationship22 that has allowed France to meddle in the internal politics of Francophone African countries. Abdurrahim Siradag23 has estimated that between 1960 and 2013 France intervened militarily in Francophone African countries twenty five times to defend beleaguered governments it favoured or get rid of those it disliked. Francophone African leaders buy security protection from French governments. Robert Bourgi,24 a confidant of many Francophone African leaders, with strong links to the French political establishment, recently revealed in his memoir, ‘They Know I Know Everything’: My Life in The Eye of Relationship Between France and Africa, that African leaders contribute financially to French political parties during French elections. An additional factor in French power and influence is the global spread of the French language. Francophone Africa is the only region in the world where the French language is still growing. As literacy levels increase in Africa, so the use of colonial languages expands. English, French and Portuguese have been adopted as official languages, even though African languages serve as lingua franca in most countries. It is reckoned that more than 300 million people in Africa speak French, at various levels of fluency, representing 67 per cent of the French-speaking population in the world. In other words, four and a half times more people speak French in Africa than in France. What has often been ignored or underreported in discussions on French neocolonialism in Africa is the strategic value of France’s close ties with its ex-colonies and why France goes to great lengths to defend those ties. The strategic objective of those economic, military and cultural ties is to embed French power in Africa and signal to the world that it is still a great power. In terms of economic importance, Nigeria offers more opportunities to France than do its Francophone West African countries, whose combined wealth (or GDP) is much less than Nigeria’s. This is why Nigeria is France’s largest trading partner in sub-Saharan Africa. However, from a strategic point of view, France cannot pivot to Nigeria to enhance its power in the world system. It faces far stronger competitors in that country than in Francophone West Africa, and it cannot craft in Nigeria the kinds of neocolonial relations it has established in Francophone Africa. To understand the logic behind France’s neocolonial designs in Africa, one must highlight France’s declining status in the world system and its long-running obsession with global great-power status.25 Between the seventeenth and nineteenth centuries, France was the preeminent power in Europe and French was the language of the educated classes, royal courts and diplomacy. French power reached its peak in the late eighteenth and early nineteenth centuries (roughly 1794–1815) when, under Napoleon, it controlled much of northern Europe. After Napoleon’s defeat in 1815 and France’s humiliating defeat by Germany under Bismarck in 1870,26 French power began to decline. But more important for our analysis was Nazi Germany’s comprehensive defeat of France in the Second World War, when the French army spectacularly collapsed without putting up a fight and allowed Hitler to set up a puppet regime in Vichy to govern France. Charles de Gaulle did establish a resistance government in exile – first in London and later in Algiers – and joined the Allied Powers to reclaim France and defeat Germany. But the collapse of France shocked the Allied Powers. France was not invited to the talks that led to the creation of the United Nations. In the eyes of the US, Britain, the Soviet Union and China – the four countries that participated in the deliberations – France had lost its status as a great power when it was occupied by Germany.27 Therefore, it didn’t deserve to be at the talks. However, Winston Churchill convinced the US president, Franklin Roosevelt, to offer France a seat on the proposed Security Council of the UN on the strength of its historical status as a great power and its big global empire, much of it in Africa. De Gaulle and the French elite felt deeply hurt by France’s decline and treatment by the victorious great powers. For much of his rule, De Gaulle was obsessed with restoring France as a great power in the comity of nations. He loathed the special relationship between the UK and the US and held steadfastly onto France’s colonies or devised neocolonial arrangements with them to keep them in France’s orbit. He also worked hard to rebuild French power within Europe by partnering with Germany to create the European Economic Community (EEC, the present-day European Union, or EU), which he felt would enhance French power and serve as a counterweight to US power and the US–UK special relationship. Twice, De Gaulle vetoed Britain’s attempt to join the EEC (in 1963 and 1967) on the grounds that the UK was not European enough. He pulled France out of the military wing of NATO in 1966 and developed France’s own nuclear deterrence. Moreover, fearing a collapse of the Bretton Woods monetary system, which was based on a gold–dollar fixed rate of exchange, he tried to protect France’s dollar reserves and undermine the dollar’s role as a global currency between 1963 and 1966 by converting many of France’s dollar holdings into gold. According to Jan Nieuwenhuijs,28 forty-four boat trips and 129 flights were made to transport 3,313 tonnes of gold reserves from the US to France. Despite these initiatives, France could not become the hegemon in the EEC because Germany’s economy was bigger and more productive than France’s, and the EEC couldn’t displace or challenge US global hegemony. The inevitability of conflict or rivalry between France and Nigeria The two sections above lay the groundwork for understanding how Nigeria and France perceive themselves as great powers. Nigeria’s power resources are much smaller than France’s. Nigeria therefore does not aspire to be a global power. But given the size of its population and economy in comparison with other African countries, it clearly aspires to be, and sees itself as, a regional power in West Africa and a top-rank power in wider Africa, where it is challenged by South Africa and, to some extent, Egypt. Nigeria’s strategic policy in the West African region can be described as expansionist. Even though it accounts for half of the population and wealth of the region, its influence in territorial terms tends to be limited to less than 10 per cent of the region’s land mass. It must expand its territorial reach if its claim to regional leadership is to be taken seriously. It is important to state that this expansionist policy is not based on aggression or territorial claims. It is pursued instead through the medium of regional integration in ECOWAS. As the biggest economy in the region, faster regional integration expands Nigeria’s economic and political influence within the Francophone states. Nigeria has supplemented the ECOWAS integration approach with bilateral assistance, such as supplying electricity to Niger and oil price discounts to a number of countries during crises. France’s global power status depends on its ability to project power globally. Its ex-colonies, most of which are in Africa, play a crucial role in helping it to do so. Three-fifths of France’s ex-colonies in Africa are in West Africa, which makes it an important region for France in projecting its image as a global power. This means that France seeks to be both a global power and a regional power in West Africa. Success in the latter feeds its ambitions in the former. However, it must contend with Nigeria, which is much bigger in population and economic terms than all the nine Francophone West African countries combined and has the added advantage of geographical propinquity that France lacks. Therefore, the strategic policy of France in West Africa is containment – to prevent Nigeria from extending its reach and influence within the Francophone countries. This policy involves undermining initiatives to deepen economic integration in ECOWAS, which would bolster Nigeria’s power within the region; supporting attempts to fragment or break up Nigeria, as it did in the civil war of the 1960s; and preventing Nigeria from playing a lead role in settling conflicts in Francophone African countries. In December 2019, following growing opposition to the monetary arrangements that underpinned the CFA franc in West Africa, and amid fears that the proposed ECOWAS eco would end the CFA franc as a currency and French economic influence in the region, Emmanuel Macron of France and Alhasan Ouattara of Côte d’Ivoire hurriedly announced new rules for the monetary system and renamed the CFA franc the eco. This was a clear challenge to ECOWAS and made it difficult for it to forge ahead with its own currency plan. Nigeria could not mount an effective campaign against the appropriation of the eco name by Ouatarra and Macron because it could not meet the convergence principles that member states had agreed on as necessary for the introduction of the eco. As the largest economy in the region, Nigeria has been unable to pursue fiscal discipline, despite the existence of a Fiscal Responsbility Law and a Fiscal Responsibility Commission established in 2007, just after the massive debt relief by the Paris Club of creditors. Muhammadu Buhari’s government announced in 2020 that Nigeria was not ready for the implementation of the eco, which was set to take off that year. France outmanoeuvred Nigeria in the Côte d’Ivoire crisis of 2010–2011, when it sent troops to topple the recalcitrant regime of Laurent Gbagbo. It did so again in the Sahel, especially in Mali, when it launched Operation Serval in 2012 to bolster the Malian regime and prevent Islamist forces from overrunning the capital. Emboldened by this success, France launched Operation Berkhané in 2014 as a counterterrorism force for the Sahel and pressured five French-speaking Sahel states – Niger, Burkina Faso, Mali, Chad and Mauritania – to form the G5 and partner with France to combat terrorism in the region. The EU also became involved in the project under its Common Security and Defence Policy and established a Regional Coordination and Advisory Cell in Mauritania. The US backed these moves by building a drone base in the south of Niger. Nigeria, the assumed regional hegemon, was excluded from the G5 and the overall French and EU-led strategy of combating terrorism in the region – an outcome which Tuggar, Nigeria’s foreign minister, bemoaned in his 2024 Premium Times29 article. The European countries were given the freedom to cut anti-immigration deals with some of the G5 states which, as Tuggar starkly observed in his article, violated the ECOWAS protocol on free movement of people in the region. However, Nigeria did nothing to check it. But then the entire France-led Western security strategy in the Sahel was upended in 2022 and 2023 when Mali, Niger and Burkina Faso asked France, the US and the EU to close their military bases and end their activities in the region. The question may be asked why France decided to support Nigeria when it threatened to lead an ECOWAS invasion of Niger in 2023 if it had always tried to keep Nigeria out of the security affairs of the Francophone states. France did so because it had lost its influence among the Nigerien armed forces and public at large, and the specific aim of the Nigeria-led ECOWAS intervention force was to restore to power in Niger a pliant French ally, Mohammed Bazoum. France might have calculated that the ECOWAS force would withdraw after Bazoum’s restoration and that Niger would return to the status quo ante, or business as usual, with France once again in charge. So, what we see when we take a cold hard look at Nigeria’s relations with France in West Africa is a clash of two strategies: Nigerian expansionism, through ECOWAS, to wean Francophone West Africa off France, and French containment of Nigeria in the subregion. From a hard-nosed realist perspective, if I were sitting at the Élysée Palace in Paris, I would be very happy with the decision by Mali, Niger and Burkina Faso to exit ECOWAS since the strategic goal of France has always been to stall, weaken or dismantle that organisation, which it believes primarily promotes Nigeria’s power in France’s assumed sphere of influence. As a French strategist, I would also be happy that the Alliance of Sahel States (AES) countries are in a conflicted relationship with Nigeria, France’s greatest competitor in the region. The last thing that France wants is for those countries to pivot towards Nigeria at a time when French influence in the region is in crisis. I would like to throw in another strategic insight: the diplomatic love affair between Tinubu and Macron may have been orchestrated by Macron to drive a wedge between Nigeria and the AES countries at a time when France’s influence in the region was diminishing. The lavish treatment Tinubu was accorded by Macron during his official visit to Paris in November 2024, at which a French band even played P-Square’s popular Afrobeats song, ‘Taste the Money’ (which has the outrageously materialistic and crass line ‘Je m’appelle chop money’), underscores the lengths to which Macron went to flatter Tinubu. Many Nigerians wondered how a song with such undignified lyrics could have been played for a visiting Nigerian president if France saw Nigeria as a serious country and partner. The French may have been exploiting the unserious part of the Nigerian power elite. Following the visit, Nigeria’s Finance Minister, Wale Edun, announced that Nigeria had secured a EUR 300 million development partnership agreement with France, which would boost key sectors of the Nigerian economy, including healthcare, transportation and renewable energy.30 France fears Nigeria more than Russia, which has jumped in to provide military support to the AES countries. Russia lacks the regional network and soft power to dominate those countries in the long run, and there is still a good amount of French power in those countries, which could be activated when Russia’s relations with them sour. Economic and cultural ties take time to adjust to new power dynamics, despite the rhetoric by the military leaders of the AES countries of a complete break with France. France, thus, is playing the long game, which requires tying Nigeria’s hands and preventing it from embracing its natural neighbours and advancing its strategic interests in the region. Dysfunctional and transactional domestic politics What comes out of this discussion is the inevitability of conflict or rivalry between France and Nigeria as each tries to be the hegemon in the West African subregion. This conflict can be checked or diffused only if Nigeria becomes so distracted and weakened that it stops seeing itself, or acting as, a subregional power. Alternatively, France must come to the realisation that it is no longer a global power, should align its foreign policy ambitions with its actual status as a highly degraded former imperial power, and start behaving like Spain, Portugal, Italy and Türkiye, which were powerful imperial powers in centuries past but no longer aspire to be world powers. Nigeria’s domestic economic troubles, political inertia and current behaviour at the global level suggest that it is more likely to cave than France. I would like to suggest that the glorification of pragmatism in Nigeria’s foreign policy, discussed in the first part of this article, may reflect a loss of focus or drift in how Nigeria’s policymakers perceive its role and project it in the world. A retired Nigerian ambassador responded to my first article by drawing attention to the problems that Nigeria’s Ministry of Foreign Affairs has faced in the last two or more decades: poor funding, long delays in the appointment of ambassadors, low morale, tardy responses to global events, and lack of a clear policy direction. That ambassador believes that most of Nigeria’s big foreign policy initiatives were undertaken during the period of military rule, not during the Fourth Republic of so-called democratic governance. Many of these points rhyme with those raised in a recent brief by the Crisis Group on Nigeria’s declining role in world affairs, although the Crisis Group dates the beginning of the rot to the period after Obasanjo’s government of 1999–2007.31 I don’t wish to get into these issues since I have not studied the internal workings of the foreign ministry. However, it would be surprising if the foreign ministry were insulted by the complaints of many scholars, pundits and ordinary Nigerians about the dysfunction of Nigerian politics, its high levels of corruption and multiple insecurities. At the heart of this dysfunction is the way politics has been purged of values and policy direction or ideology and reduced to mere transactions for self-enrichment. Jibrin Ibrahim, a former director of the Centre for Democracy and Development, captures this sad situation in his book chapter, ‘Democratic regression, political parties, and the negation of the popularity principle’,32 and more recently in a Premium Times article,33 in which he laments the degeneration of Nigeria’s party system. Large-scale cross-carpeting is rife, with opposition party members moving to the governing party for material returns after every election; powerful figures act as godfathers in political parties and engage in wheeling and dealing during party primaries to rig elections in favour of their candidates; and legislators are accused of extracting payments from heads of agencies before the approval of their budgets. Nigeria clearly lost its bearings when it was egged on by two of France’s client leaders in Africa, Alhassan Ouattara of Côte d’Ivoire and Macky Sall of Senegal, to wage war against a neighbour with whom it shares a more than 1,608-kilometre border and close cultural ties, under the pretext that it was trying to restore democracy in that country. That threat, which eventually fizzled out, was a strategic policy blunder of historic significance. It is likely to have far-reaching effects on Nigeria’s leadership role in the subregion. What made the decision even more ludicrous was that Ouattara and Sall are no democrats – Ouattara changed his country’s Constitution to run for a third term as president and is reported to be considering a fourth term; and Sall gave up on his aggressive quest for a third term in office only when he was confronted by sustained mass protests. Tinubu’s electoral victory in 2023 was also questionable. The Independent National Electoral Commission (INEC) Result Viewing Portal (IRev), which the chief electoral officer, Mahmood Yakubu, promised would transmit the presidential results in real time, failed to function. Many INEC officials claimed they had forgotten their passwords or could not upload the results in real time.34 Indeed, Tinubu’s victory was seriously being contested in court when he made the decision to get ECOWAS to invade Niger. The argument has been made about Nigeria’s overlapping interests and need to be pragmatic in dealing not only with France but also with global economic blocs or formations, such as BRICS. It is important to note that of the ten full or permanent members of BRICS (Brazil, Russia, India, China, South Africa, Saudi Arabia, United Arab Emirates, Iran and Ethiopia), only Ethiopia, and Iran and Russia, both of which are under stiff US sanctions, have lower volumes of trade and investments with the US than Nigeria. The others trade heavily with the US – far more than Nigeria, which is timid in asking for full membership, preferring to play a waiting game in the name of pragmatism. Indeed, close US allies, such as Saudi Arabia and the United Arab Emirates (UAE), which have high levels of trade and investments with the US, are not constrained by their overlapping interests in deciding to seek and obtain full membership of BRICS. It should be noted that, among other objectives, BRICS aims to counter the weaponisation of the dollar, in which the US and its Western allies freeze the foreign exchange reserves of countries with which they strongly disagree. Although most of the BRICS countries have economic relationships with the US and the rest of the world, they believe that it is in their strategic interest to find ways of financing their trade relations without being overly exposed to the US dollar. They’re still pragmatic in nurturing their trade relations but have adopted the strategic or long-term view that dependence on the US is bad for their economic development. The pitfalls of transactional foreign policy I would like to address two big problems associated with transactional foreign policy, a concept that has gained importance in recent years in the study of global politics. Galib Bashirov,35 in his article ‘The Rise of Transactionalism in International Relations’, defines transactionalism as a foreign policy approach that favours bilateral to multilateral relations, focuses on short-term wins rather than longer-term strategic foresight, adheres to a zero-sum worldview where all gains are relative and reciprocity is absent, rejects value-based policymaking, and does not follow a grand strategy. Even though Bashirov’s article focuses on Türkiye, it is the US’s Donald Trump that has been more closely identified with transactionalism as he seeks to upend alliances and treaties by insisting on short-term wins for the US in his dealings with friendly countries and enemies. If we remove the reference to multilateralism, which small states fully embrace to maximise returns in global institutions they contribute very little to financially, almost by definition the foreign policies of small or inconsequential states tend to be transactional. Such states want to get along with all big powers to squeeze out whatever trade, investment and aid benefits they can from the global system. As we have also observed, such states may decide to become vassal states of one big global power if they believe that shopping around is likely to yield fewer returns than picking one powerful patron. During the Cold War, for instance, South Korea and Taiwan were vassal states of the US, which protected them from Communist North Korea and China and facilitated their transformation into industrial states. Most small countries in the world prefer a ‘neutral, shop-around approach’ to vassalship. For example, especially in recent times, the foreign policy of my own country, Sierra Leone, is heavily transactional as it tries to stay in the good books of most big powers and blocs in its search for aid and investments. This transactional approach even means repudiating longstanding African Union policy positions, such as declaring its intention to open an embassy in Jerusalem (before Israel’s genocidal carnage in Gaza) and its controversial decision to recognise Morocco’s sovereignty over Western Sahara as demanded by Morocco and the US. It is important to note that only six countries (the US, Guatemala, Paraguay, Honduras, Kosovo and Papua New Guinea) have embassies in Jerusalem. And it was at the 1980 Organisation of African Unity (OAU) Summit in Freetown, Sierra Leone, that the Saharawi Arab Democratic Republic (SADR) first gained majority recognition by African states, even though the chair of the conference, Siera Leone’s Siaka Stevens, who supported the SADR, decided to postpone the decision on its membership of the OAU.36 The SADR was admitted into the OAU in 1982 and currently enjoys the support of most members of the organisation, including big or influential powers, such as Nigeria, South Africa, Ethiopia, Tanzania and Kenya. Meanwhile, Sierra Leone also has good relations with China, Türkiye, Russia, the UAE and Saudi Arabia, apart from its long-established relations with the EU and UK. Since small inconsequential states lack ambitions to be great powers, they treat the world system as a marketplace that does not require values, strategic goals or principles to transact business in. So, one of the pitfalls of transactionalism in foreign policy for states that harbour regional power ambitions is the high risk that they will be reduced to small states – big in size and resources but small on the world stage. It is important to stress that size on its own is not sufficient for a state to enjoy the status of a big or regional power. Adekeye Adebajo,37 in his edited book with Abdul Raufu Mustapha, once described Nigeria, in discussing its foreign policy, as ‘a giant with clay feet’ or Jonathan Swift’s Gulliver who was overwhelmed by Lilliputians. Population wise, the Democratic Republic of Congo (DRC) is more than seven times the size of Rwanda and has about five times its GDP, but political dysfunction in the DRC has allowed Rwanda to turn eastern DRC into its playground. Based on recent international reports, the Rwandan government, acting through its M23 militia, is stoking instability and insecurity in that region without an effective response from Kinshasa. The second problem with a transactional approach to foreign policy is that it may be exposed to high levels of corruption and illicit activities, especially if these activities already exist in their countries. The foreign policy practitioners of transactional states may engage in deals that primarily serve their own rather than the national interest; and even when projects may be good for their country, their costs may be inflated through bribes paid to state officials who are responsible for sealing the deals. A more worrying problem is illicit transactions – such as drug and human trafficking, as well as money laundering. Two diplomatic scandals have unfolded in Sierra Leone over the past month, in which high-level state officials have been implicated in trafficking cocaine. The first is the interception in Guinea of a diplomatic vehicle owned by the Sierra Leonean ambassador to Guinea, which was carrying seven suitcases of cocaine;38 the second involves the sighting in Sierra Leone of Europe’s most wanted drug criminal, Jos Leijdekkers, who has been sentenced to a prison term of twenty-four years in the Netherlands for trafficking seven tonnes of cocaine to Europe.39 He was videoed sitting with the president’s daughter (who is believed to be romantically linked with him) two rows behind the president at a church service in the president’s hometown, and at a farm in the same town participating with the president, his daughter and villagers in rice harvesting. Conclusion Nigeria’s foreign policy seems to have become more transactional than strategic in recent years. This has been justified by some scholars and pundits as pragmatism, which they argue is necessary in a complex and changing world. We have shown that pragmatism is a poor guide for understanding the foreign policies of states, since all states act pragmatically in the world system. Understanding the power resources of states, their geographical location and interests is crucial in the study of foreign policy. Nigeria and France historically have been locked in a power struggle for control of the West African region. As the largest and richest economy in the subregion, and especially after the oil boom of the early 1970s, Nigeria has pursued an expansionist foreign policy through the medium of ECOWAS to advance its development and wean the Francophone West African states off France. France’s strategic interests in West Africa are tied to its higher strategic goal of remaining a global power. Since it is not located in the region, which would have allowed it to expand its influence as the richer and more powerful country, it practises a policy of containment against Nigeria to maintain its neocolonial hold on its ex-colonies. Nigeria’s internal political dysfunction, economic troubles and drift towards a transactional foreign policy have tilted the power balance in the region in favour of France. Nigeria has failed to exploit the recent military and diplomatic setbacks by France in the region, preferring instead to fully embrace France as a partner. France benefits from this rapprochement and the seeming breakup of ECOWAS. The breakup of ECOWAS prevents the AES countries, which are trying to move away from France, from pivoting to Nigeria. As an aspiring regional power, Nigeria should be wary of two major pitfalls of transactionalism in foreign policy: a slide into the status of a small state and its treatment as such by the big powers; and the danger of transactionalism pushing the state to the seamy or illicit domains of international relations. Notes 1 Y. Bangura, 2025, ‘What’s gone wrong with Nigeria’s foreign policy’, Premium Times, 21 January; Daily Trust, 22 January; Intervention, 20 January. 2 M. Al-Ghazali, 2025, ‘Bangura’s perspective on Nigeria’s BRICS’s classification’, Daily Trust. 24 January. 3 T. Alabi, 2025, ‘Yusuf Bangura on Nigeria’s Foreign Policy, France and Brics’, Future World, 26 January 4 Channels, ‘Trump’s inaugural address, the worst in History—Prof. Akinyemi’. https://www.youtube.com/watch?v=0CcbdQZ8vrc 5 M. Imam, 2025, ‘Re: What’s gone wrong with Nigeria’s foreign policy?’ Daily Trust, 27 January. 6 Y. Tuggar, 2025, ‘Foreign policy and the path to peace in a dangerous neighbourhood’, Premium Times, 8 January. 7 F. Mimiko, 2024, ‘The 4D thrust in Nigeria’s foreign policy’, Premium Times, 3 April. 8 J. Measheimer, 2001, The Tragedy of Great Power Politics. New York: W.W. Norton Company. 9 T. Schelling, 1960, The Strategy of Conflict, The Strategy of Conflict. New York: Pickle Partners Publishing. 10 Y. Bangura, 1994, ‘Intellectuals, Economic Reform and Social Change: Constraints and Opportunities in the Formation of a Nigerian Technocracy’, Development and Change, Vol. 25, No. 2, pp. 261–305. 11 M. R. Koutonin, 2022, ‘Nigeria’s Role in Ending Apartheid in South Africa’, MSINGI. 1 February 2022. https://www.msingiafrikamagazine.com/2022/02/nigerias-role-in-ending-apartheid-in-south-afrika/ 12 N. Ngwenya, 2010, ‘Giants of Africa Limp Along--South Africa and Nigeria’, SAIIA 90 Years. Pretoria: South African Institute of International Affairs. https://www.google.com/search?q=giants+of+africa+limp+along&oq=giants+of+africa+limp+along&gs_lcrp=EgZjaHJvbWUyBggAEEUYOTIHCAEQIRigAdIBCDk2NzlqMGo0qAIAsAIA&sourceid=chrome&ie=UTF-8—. 13 M. Wyss, 2016, ‘A Post-Imperial Cold War Paradox: The Anglo-Nigerian Defence Agreement 1958-62’, The Journal of Imperial and Commonwealth History, Vol. 44, No. 6, pp.. 976–1000. 14 M. R. Koutonin, 2022, ‘Nigeria’s Role in Ending Apartheid in South Africa’, MSINGI. 1 February 2022. https://www.msingiafrikamagazine.com/2022/02/nigerias-role-in-ending-apartheid-in-south-afrika/ 15 Economic Commission for Africa, ‘Mr. Adebayo Adedeji’. https://www.uneca.org/ess/mr-adebayo-adedeji 16 I. Gambari, 1986, ‘Nigerian Foreign Policy Since Independence’, Nigerian Journal of Policy and Strategy, pp 76–89. 17 B. Akinyemi, 1987, ‘Concert of Medium Powers Revisited’, New Nigerian. 4 May. 18 C. Obi, 2009, ‘Economic Community of West African States on the Ground: Comparing Peacekeeping in Liberia, Sierra Leone, Guinea Bissau, and Cote d’Ivoire. African Security, Vol 2, Issue 2-3, pp. 119–135. 19 Crisis Group, 2024, ‘Restoring Nigeria’s Leadership for Regional Peace and Security’, Briefing No. 203. Dakar/Brussels. 11 December. https://www.crisisgroup.org/africa/west-africa/nigeria/b203-restoring-nigerias-leadership-regional-peace-security 20 Banque Centrale des Etats de l’Afrique de l’Ouest; and Banque des Etats de l’Afrique Centrale. 21 F. Pigeaud and N. S. Sylla, 2021, Africa’s Last Colonial Currency: The CFA Franc Story. London: Pluto Press. 22 For a useful in-depth study of France’s relations with Africa during the decolonisation period, see: Tom Chafer, The End of Empire in French West Africa: France’s Successful Decolonization? Oxford and New York: Berg. 23 A. Siradag 2014, ‘Understanding French Foreign and Security Policy Towards Africa: Pragmatism or Altruism’,Afro Asian Studies Journal, Vol. 3, No. 1, pp. 100–122. 24 R. Bourgi 2024, ‘They Know I Know Everything’: My Life in The Eye of Relationship Between France and Africa. Paris: Max Milo Editions. 25 The following book provides rich insights on De Gaulle’s obsession with projecting France as a world power: Jonathan Fenby, 2010, The General: Charles de Gaulle and the France He Saved, New York: Simon and Schuster. 26 P. Boniface, 2001, ‘Is France Still a World Power?’ Centre for International Relations, Queens University, Canada. 27 G. Heimann, 2014, ‘What Does it Take to Be a Great Power? The Story of France Joining the Big Five’, Review of International Studies, Vol. 41, No. 1, pp. 185–206. 28 J. Nieuwenhuijs, 2024, ‘How France Secretly Repatriated All Its Gold Before Nixon’s Dollar Devaluation’. GEP: GULL ER PENGER. 8 October. https://www.gullerpenger.no/publikasjoner/artikler/how-france-secretly-repatriated-all-its-gold-before-nixon-s-dollar-devaluation-2024-10-08/ 29 Y. Tuggar, 2025, ‘Foreign Policy and the Path to Peace in a Dangerous Neighbourhood’, Premium Times. 8 January. 30 S. Anyanwu, 2024, ‘FG Secures E300 Million Development Partnership with France’, 29 November. Federal Ministry of Information and National Orientation. https://fmino.gov.ng/fg-secures-e300-million-development- partnership-with-france/#:~:text=In%20a%20landmark%20move%20to,%2C%20transportation%2C%20and%20renewable%20energy. 31 Crisis Group, 2024. 32 J. Ibrahim, 2023, ‘Democratic regression, political parties, and the negation of the popularity principle’, in W. Adebanwi (ed.), Democracy and Nigeria’s Fourth Republic: Governance, Political Economy and Party Politics. Woodbridge: James Currey. 33 J. Ibrahim, 2025, ‘The Nigerian Party System, a Danger to Democracy’, Premium Times. 24 January. 34 M. Acheampong, 2023, ‘Overpromising and Underdelivering? Digital Technology in Nigeria’s 2023 Presidential Elections’. German Institute for Global and Area Studies (GIGA). GIGA Focus Africa. No. 2. https://www.giga-hamburg.de/de/publikationen/giga-focus/overpromising-underdelivering-digital-technology-nigerias-2023-presidential-elections 35 G. Bashirov, 2019, ‘The Rise of Transactionalism in International Relations: Evidence from Turkey’s Relations with the European Union’, Australian Journal of International Affairs. Vol. 74, No. 2, pp. 165–184. 36 I’m grateful to Ismail Rashid, professor of History at Vassar College, USA, for drawing my attention to this point. For details see: J. Naldi, 1982, ‘The Organization of African Unity and The Saharawi Arab Democratic Republic’, Journal of African Law, Vol. 26, No. 2, pp. 152–162. 37 A. Adebajo and A. R. Mustapha (eds), 2008, Gulliver’s Troubles: Nigeria’s Foreign Policy After the Cold War. Pietermaritzburg: University of KwaZulu-Natal Press. 38 M. Wycliffe, 2025, ‘Suitcases of “cocaine” found in Sierra Embassy vehicle’, BBC. 12 January. https://www.bbc.com/news/articles/cn4zzq1vk87o 39 J. Rankin, 2025, ‘One of Europe’s most wanted drug traffickers living in Sierra Leone, say Dutch prosecutors’, The Guardian, 27 January. https://www.theguardian.com/society/2025/jan/27/one-of-europes-most-wanted-drug-traffickers-living-in-sierra-leone-say-dutch-prosecutors. See also Africa Confidential 2025, ‘President Bio keeps cocaine lord in the family’. February. https://www.africa-confidential.com/uploads/content/Sierra%20Leone%20Cocaine%20Lord%20Special%20Report.pdf